2010
DOI: 10.1021/jp909202u
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation of Surfactin Derivatives at the Decane/Water Interface at Low Surface Coverage

Abstract: Interfacial behavior of surfactin methyl ester derivatives at the n-decane/water interface at low surface coverage has been studied by molecular dynamics simulation. Molecular orientations, structural variability of the peptide ring backbones, interfacial molecular areas, and the motion activities of surfactin derivatives have been determined. The simulations show that surfactin monomethyl ester stands vertically at the oil/water interface compared with surfactin molecule. The aliphatic chains tilt at the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 40 publications
2
23
0
Order By: Relevance
“…For instance, Mu et al studied the interfacial behavior of surfactin methyl ester derivatives at the n-decane/ water interface at low surface coverage by MD simulation. Molecular orientations, structural variability of the peptide ring backbones, interfacial molecular areas, and the motion activities of surfactin derivatives were determined [28]. Dai et al reported the MD simulation of the in situ self-assembly of nanoparticles and SDS surfactants at a water/trichloroethylene (TCE) interface, highlighting the potential of using the liquid/liquid interface to produce novel nanomaterials [29].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Mu et al studied the interfacial behavior of surfactin methyl ester derivatives at the n-decane/ water interface at low surface coverage by MD simulation. Molecular orientations, structural variability of the peptide ring backbones, interfacial molecular areas, and the motion activities of surfactin derivatives were determined [28]. Dai et al reported the MD simulation of the in situ self-assembly of nanoparticles and SDS surfactants at a water/trichloroethylene (TCE) interface, highlighting the potential of using the liquid/liquid interface to produce novel nanomaterials [29].…”
Section: Introductionmentioning
confidence: 99%
“…2 and S1), and density distributions of water and n ‐decane were fitted by hyperbolic tangent functions (Vashishat et al, 2016) as follows, ρ()z=12ρL±12ρLtanh[]()zz0/d where ρ L is the bulk density, z 0 and d are the position and width of the water or n ‐decane interface. The interface region of n ‐decane/surfactant/water was located between the position that was 90% of the mass density of bulk n ‐decane density and that of bulk water density according to the 10–90 criteria (Gang et al, 2010b). Density distributions of different groups of surfactants were fitted by Gaussian function ρ()z=ρmaxexp[]()zzC22σ2 where z C is the position of the peak center, and σ is the width of each peak.…”
Section: Resultsmentioning
confidence: 99%
“…where ρ L is the bulk density, z 0 and d are the position and width of the water or n-decane interface. The interface region of n-decane/surfactant/water was located between the position that was 90% of the mass density of bulk n-decane density and that of bulk water density according to the 10-90 criteria (Gang et al, 2010b). Density distributions of different groups of surfactants were fitted by Gaussian function…”
Section: Structure Of Surfactant Monolayersmentioning
confidence: 99%
“…The interfacial behaviour of surfactin depends on the pH of the aqueous phase, with greater conformational freedom being found for low pH due to the decreased hydrophilicity of the Glu and Asp residues when these become protonated [118]. This can also been seen when surfactin derivatives with methyl ester groups added to the Glu and Asp residues [119].…”
Section: Surfactin and Other Lipopeptidesmentioning
confidence: 99%